Desarrollo de una bebida hidratante a partir de lactosuero. - Canchig Romero, William Paúl (2022)
This project was developed at the Technical University of Cotopaxi, Faculty of Agricultural Sciences and Natural Resources of the Agroindustrial Engineering Career, which had the objective of developing a hydrating drink from whey and blueberry pulp using different sugars (panela, stevia and sucralose). After studying the methodology for the preparation of a hydrating drink, it was carried out at the Agroindustrial Engineering plant, in addition to the food laboratory of the Technical University of Cotopaxi. A 3x2 factorial design was proposed under a completely randomized block design (DBCA). Having two factors, Factor A (concentration of whey and blueberry pulp) and factor B (types of sweeteners), once the treatments were carried out with their respective repetitions, the physical-chemical factors such as pH, titratable acidity and soluble solids in a time of 7 days, once the measurements were obtained, we proceeded to analyze each day by entering the data into the InfoStat statistical tool, this allowed us to appreciate how the treatments interacted and helped determine the best treatments (t1, t6, t7, t8, t9). A sensory analysis was carried out with the help of 10 students of the Agroindustrial Engineering Career, through tastings where a descriptive method was proposed to evaluate according to a hedonic scale with values from 1 to 5 (color, smell, taste, texture and acceptability ) of the moisturizing drink, it was possible to determine that the best treatment was t6 (a2b3), which corresponds to (50% whey, 50% blueberry pulp + stevia), obtaining physical chemical parameters such as pH (4), soluble solids (10.5º Brix), titratable acidity (0.08%), osmolality (402,5 mOsm/L), sodium (10.25 mEq/L), potassium (24.18 mEq/L), magnesium (6, 68 mEq /L), calcium (7.82 mEq /L), microbiological requirements obtained such as: Total aerobic count in CFU (47 x 101), Total coliform count in CFU (< 10), Mold count in CFU (< 10) and yeast count in CFU (30 x 101 cfu/ml) and a nutritional analysis obtained parameters such as fat 0.00%, protein 0.23%, crude fiber 0.00%, ash 0.00%, cholesterol 0.00 mg/100g, sodium 308.95 mg/kg, solids total 9.39%, carbohydrates 8.78%, calories of 36.04 Kcal/100 g, while a total sugar profile of 5.66% obtaining fructose with 2.87%, glucose 2.79%, sucrose 0 .00% and lactose 0.00%, therefore it agrees with the specifications required in the Colombian Technical Standard 3837, the Mexican Official Standard NOM 218-SSA1-2011 and the Ecuadorian Technical Standard NTE INEN 2411, NTE INEN 2304. The value for a 350 ml bottle it has a retail price of $1.84 cents.